Critical comparison of the on‐line and off‐line molecularly imprinted solid‐phase extraction of patulin coupled with liquid chromatography. Issue 23 (2nd November 2017) - Lhotská, Ivona; Holznerová, Anežka; Solich, Petr; Šatínský, Dalibor
Abstract: Reaching trace amounts of mycotoxin contamination requires sensitive and selective analytical tools for their determination. Improving the selectivity of sample pretreatment steps covering new and modern extraction techniques is one way to achieve it. Molecularly imprinted polymers as selective sorbent for extraction undoubtedly meet these criteria. The presented work is focused on the hyphenation of on‐line molecularly imprinted solid‐phase extraction with a chromatography system using a column‐switching approach. Making a critical comparison with a simultaneously developed off‐line extraction procedure, evaluation of pros and cons of each method, and determining the reliability of both methods on a real sample analysis were carried out. Both high‐performance liquid chromatography methods, using off‐line extraction on molecularly imprinted polymer and an on‐line column‐switching approach, were validated, and the validation results were compared against each other. Although automation leads to significant time savings, fewer human errors, and required no handling of toxic solvents, it reached worse detection limits (15 versus 6 μg/L), worse recovery values (68.3–123.5 versus 81.2–109.9%), and worse efficiency throughout the entire clean‐up process in comparison with the off‐line extraction method. The difficulties encountered, the compromises made during the optimization of on‐line coupling and their critical evaluation are presented in detail.